Could Telling Parents About Substance Use Decrease Involvement in Crime of Substance Users? - Danışman, Mustafa; İspir, Gamze Zengin; Özpolat, Ayşe Gül Yılmaz (Fortschritte der Neurologie · Psychiatrie, 2023)
Introduction Substance use disorder and criminal behaviors are increasing all over the world day by day. Factors that affect the involvement in crime among people with substance use disorders need to be examined more. This research aims to investigate the protective factors of substance users’ involvement in crime and clarify the importance of telling parents about their substance use.Method A total of 190 patients with substance use disorders were included. Patients were divided into two groups: those who told their families about their substance use (TP+) and those who did not tell (TP-). A sociodemographic data form, the short form of My Memories of Upbringing Scale for perceived parental attitudes, Experiences in Close Relationships Scale-Revised, and Emotional Autonomy Scale were used.Results Our study found that people in the TP+group were less involved in crime than TP-. Telling rates increased proportionally when individuals' anxious attachment and individuation levels rose. In the TP+group, criminal history was correlated positively with substance use duration.Conclusion Telling their families that they are using substances can be a protective factor in itself against crime among drug users, especially in the early stages of addiction. Professionals in addiction psychiatry should encourage their patients to tell their substance use. Teaching and encouraging them to communicate with their relatives might play a key role for policymakers while dealing with substance use disorders and related outcomes.
Keywords: substance use disorder; family relations; crime; individuation